Success Factors Of Electronic Channels: An Analysis On Commercial Banks In Malaysia - Ong , Hway Boon (2002)
The impact of technology in banking is mainly felt in the delivery of banking services through electronic channels. Other than bank branches, electronic channels like ATMs, pC banking, phone banking and banking kiosks have provided other alternatives to acquire banking products and services. Nonetheless, it is not easy changing from traditional methods of banking to one that is paperless and cashless. Also, in view of the high investment cost of operating electronic channels, the return is in fact, uncertain. Therefore, the question now is what would it take to bring about success in implementing electronic distribution channels? The purpose of this study is to find out how electronic channels can be implemented successfully by domestic commercial banks in Malaysia. In order to do so, data is collecetd by self-administrated questionnaires distributed to all the domestic commercial banks in Malaysia. Data collected are analysed by means of primary statistics such as frequency, mean and mode analysis, as well as factor and Spearman correlation analysis. The factor analysis conducted indicated that banks' operation management is the main factors affecting the success of ATMs, PC and branch banking, while product innovation and knowledge development factor are found to have the most effect on the success of banking kiosks and phone banking, respectively. So to determine the association of success factors of each distribution channel, the Spearman's rank correlation is conducted but there was no significant correlation for factors identified under phone banking and branch networks. However, planning and control factor of banking kiosks is found to have an inverse association with product innovation and knowledge development factor. Besides, internal planning and control factor is discovered to cause constrain to product innovation and knowledge development in PC banking.